Shifting policies, shifting talent: U.S. immigration regulations and the global mobility of STEM students - Chen, Christina (American Journal of STEM Education, 2026)
Recent shifts in U.S. immigration policies have introduced uncertainty into the global mobility pathways of international STEM students. Changes affecting F-1 visa regulations and the Optional Practical Training (OPT) program have raised concerns about the United States’ long-term stability as a destination for international talent. This perspective article examines how policy volatility influences global STEM student flows and contributes to the redistribution of talent toward emerging study destinations. Drawing on enrollment trends and comparative international education research, the article highlights how countries such as Germany, Japan, and Finland are expanding recruitment strategies and post-study work opportunities to attract global STEM graduates.